PATTERNS OF INTERACTION BETWEENGOVERNMENT AND NON-PROFIT ORGANIZATIONS IN THE CONTEXT OF CONFLCIT RESOLUTION IN MODERN RUSSIA - V. P. Miletskiy; I. S. Lysenko (Дискурс)
The interaction of social actors, institutions of state and municipal authorities and the non-profit sector in the context of prevention, management and resolution of social conflicts is developing every year. The number of grants for such activities for socially-oriented non-profit organizations is growing. The article discusses the state of such interaction between the government and the non-profit sector concerning social conflicts, including the distribution of projects among the members of the Russian Federation, coordination of activities, target audience, the technologies implemented, and determining the place of alternative conflict resolution methods within such projects. The authors assess the features of the current interaction between the government and the non-profit sector in exploring, preventing, managing and resolving social conflicts.